1996
DOI: 10.1177/002199839603001603
|View full text |Cite
|
Sign up to set email alerts
|

Failure Behavior of Plain Weave Fabric Laminates under On-Axis Uniaxial Tensile Loading: I—Analytical Predictions

Abstract: A two-dimensional woven fabric composite strength model is presented for the prediction of failure strength of two-dimensional orthogonal plain weave fabric laminates under on-axis uniaxial static tensile loading. Different stages of failure such as warp strand transverse failure, fill strand shear/transverse failure, pure matrix block failure and the failure of matrix and fiber in the fill strand in longitudinal tension are considered. Material and geometrical nonlinearities have been considered for predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…The relative positioning of adjacent layers with the same orientation, hereafter referred to as stacking, determines the number of coincident valleys and peaks between adjacent layers and, therefore, affects strongly the degree of nesting. Very few studies have discussed the effect of stacking (and resultant nesting) on the failure of woven composites [9][10][11][12][13]. Breiling and Adams [10], studying the compressive failure of a 5H satin carbon-epoxy, concluded that varying the stacking configuration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The relative positioning of adjacent layers with the same orientation, hereafter referred to as stacking, determines the number of coincident valleys and peaks between adjacent layers and, therefore, affects strongly the degree of nesting. Very few studies have discussed the effect of stacking (and resultant nesting) on the failure of woven composites [9][10][11][12][13]. Breiling and Adams [10], studying the compressive failure of a 5H satin carbon-epoxy, concluded that varying the stacking configuration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation outcomes at least provide a theoretical guide for the design of fabric architecture. Among the simulations, Representative Volume Element (RVE) model is the most commonly employed approach [11][12][13][14][15][16][17][18]. According to the fabric architecture, the composite structure is divided into repeated cells, representing the properties and the behaviour of the whole system.…”
Section: Introductionmentioning
confidence: 99%
“…To take the actual woven fabric geometry into account, Naik and Shembekar [12] applied the parallel or series models, section by section, for the RVE of a woven-fabric laminate. This approach considers the two-dimensional extent of the fabric and was used for the study of elastic and failure behaviour of plain woven fabric laminates by Naik and Shembekar [12] and Naik and Ganesh [13]. Recently, due to the fast development of high-speed computers, three-dimensional RVEs have been used to predict the overall properties and failure behaviour of fabric composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations